Safety of betaine as a novel food pursuant to Regulation (EC) No 258/97. (17th November 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on betaine as a novel food (NF) pursuant to Regulation (EC) No 258/97. The information provided on the composition, the specifications, the batch‐to‐batch variability, stability and production process of the NF is sufficient and does not raise concerns about the safety of the NF. The NF is proposed to be used in foods intended to meet additional requirements for intense muscular effort with a maximum intake of 2.5 g/day of betaine for sports people above 10 years of age. Based on the lowest BMDL05, which was derived from a chronic toxicity study in rats in which a dose‐related increase in platelet counts was observed, and the anticipated daily intake of the NF in the target population, the Margins of Exposure are 3.6 and 5, which are generally regarded as not sufficient. However, the total exposure to betaine from the diet (about 830 mg/day) is not known to be associated with adverse effects. Moreover, no adverse effects on platelet counts were noted in human intervention studies with exposure levels of 4 g/day of betaine for up to 6 months. A significant increase in total and low‐density lipoprotein (LDL)‐cholesterol concentrations was noted at intakes of 4 g/day of betaine in overweight subjects with metabolic syndrome but not in healthy subjects, nor at intakes of 3 g/day. Thus, considering 4 g/day of betaine as a reference point and applying an uncertainty factor of 10 to account for interindividual variability, an amount of 400 mg/day of betaine (i.e. 6 mg/kg body weight (bw) per day for adults) in addition to the background exposure is considered as safe. The Panel considers that the NF is safe to be used at maximum intake of 6 mg/kg bw per day in the target population.